2019
DOI: 10.1038/s41598-019-52605-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ecological factors on the antioxidant potential and total phenol content of Scrophularia striata Boiss

Abstract: Scrophularia striata, commonly known as figwort, is one of the most important medicinal plants that mainly grows in cold regions of the Zagros Mountains (West of Iran). Although the chemical composition of this plant species has not yet been explored, people living in Ilam province (W Iran) have used it for many years to treat different illnesses. The present study aims to analyze the effect of some ecological factors on the antioxidant potential and the amount of phenol present in this plant species, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 37 publications
11
103
2
2
Order By: Relevance
“…Differently, it was the second main bioactive detected in the essential oil obtained by Ebrahimi et al 29 ; in particular, the amount was higher (12.06%) when the plant was cultivated at 1100 m above sea level and lower (5.71%) when cultivated at 2000 m above sea level. These differences confirm the key role of the environment (soil chemical composition and physiographic factors such as altitude) on the www.nature.com/scientificreports/ genetic and non-genetic variations of plants along with the production of secondary metabolites 35,36,48 . Camphor is a monoterpene, widely used in traditional and modern medicine thanks to its antimicrobial properties and beneficial effects on the cardiovascular system.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Differently, it was the second main bioactive detected in the essential oil obtained by Ebrahimi et al 29 ; in particular, the amount was higher (12.06%) when the plant was cultivated at 1100 m above sea level and lower (5.71%) when cultivated at 2000 m above sea level. These differences confirm the key role of the environment (soil chemical composition and physiographic factors such as altitude) on the www.nature.com/scientificreports/ genetic and non-genetic variations of plants along with the production of secondary metabolites 35,36,48 . Camphor is a monoterpene, widely used in traditional and modern medicine thanks to its antimicrobial properties and beneficial effects on the cardiovascular system.…”
Section: Resultssupporting
confidence: 59%
“…The yield from leaves was ~ 0.25% and that from flowers was ~ 0.28%, lower than those obtained in previous studies based on extraction of the aerial parts of this plant, but it can be connected to both the species used and climatic growth conditions 28 – 31 . Indeed, secondary metabolites are generally synthetized in plants as they represent the most important defense mechanisms against pathogens; the amount produced along with the quality may vary as a function of habitat, the organ in which they are produced and climate conditions 35 , 36 . These differences are most likely due to differences in chemotype, which are also connected to environmental and climate conditions 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Results shown in Figure 4 show that immature fruits harvested from Sevastiana had lower FCR and DPPH levels compared to immature fruits harvested from Karydia, which was not an expected finding, as it is known that phenolic compounds have antioxidant activity [70]. Zargoosh et al [71] observed the same positive correlation between DPPH and phenolic content for one out of the three regions, where they conducted their experiments for figwort (Scrophularia striata) antioxidant potential. They attributed this positive correlation to the formation of other compounds that affect the antioxidant potential of plants; however, further research is necessary for the identification of these compounds.…”
Section: Discussionmentioning
confidence: 89%
“…Although genetic processes guide the production of antioxidant compounds in plants, it is also strongly influenced by external factors. Therefore, such factors as heavy metals cause changes in the growth of plants, as well as the quantity of their antioxidant substances [15]. For example, [16] shown significant increase in antioxidant activity when plant were exposed to toxic levels of Mn.…”
Section: Discussionmentioning
confidence: 99%